Acute Effects of Ambient Particulate Matter on Blood Pressure: Differential Effects across Urban Communities - Dvonch, J. Timothy (2009)
Recent studies have suggested a link between exposure to ambient particulate matter <2.5μm in diameter (PM(2.5)) and adverse cardiovascular outcomes. The objective of this study was to examine the effects of differing community-level exposure to PM(2.5) on daily measures of blood pressure (BP) among an adult population. During the period May 2002 through April 2003, BP was examined at two time points for 347 adults residing in three distinct communities of Detroit, MI. Exposure to PM(2.5) was assessed in each community during this period, along with multivariate associations between PM(2.5) and BP. In models combining all three communities, PM(2.5) was significantly associated with systolic pressure (SP); a 10 μg/m(3) increase in daily PM(2.5) was associated with a 3.2 mm Hg increase in SP (p=0.05). However, in models that added a location interaction, larger effects were observed for SP within the community with highest PM(2.5) levels; a 10 μg/m(3) increase in daily PM(2.5) was associated with a 8.6 mm Hg increase in SP (p=0.01). We also found young age (<55 years) and not taking BP medications to be significant predictors of increased BP effects. Among those taking BP medications, the PM(2.5) effect on BP appeared to be mitigated, partially explaining the age effect, as those participants less than 55 years were less likely to take BP medications. Short-term increases in exposure to ambient PM(2.5) are associated with acute increases in BP in adults, especially within communities with elevated levels of exposure.